The limits of monetizing and paying for volunteering in eldercare: a behavioral-economic approach - Kehl, Konstantin; Stahlschmidt, Stephan (Voluntas, 2016)
The monetary value of informal eldercare in the family and voluntary sector has drawn much attention as it concerns a resource of welfare governments and nonprofit organizations try to activate via cash benefits. Studies addressing the issue in order to assess the economic impact of non-market activities and the willingness to accept financial rewards have largely ignored differences in the utility function of caregivers. Applying a behavioral-economic approach, we report a profound and formerly unobserved distinction between care in the household and non-household care for a family member or in a voluntary framework: whereas caregivers within the household perceive care as a burden and a positive shadow price arises, in the non-household context—and particularly in the volunteering case-care extends well-being and leads to negative shadow prices. The results show that non-market activities can only be measured in monetary terms to a limited extent and contribute to explaining the boundaries of monetary incentive policies.